The Aesthetic Expression for the Nanyin Music by the Lam Kwan Boen Hian Tong Community - Ulfah, Zulfia; Utomo, Udi; Triyanto, Triyanto (Catharsis, 2019)
Nanyin is a piece of Chinese traditional music. The music is preserved as anaesthetics ethnic expression of the Chinese community in Semarang. This research aims to analyze the aesthetic expression of nanyin by the Lam Kwan Boen Hiang Tong in Semarang. The research employs the method of descriptive qualitative with aesthetics approach. The data were collected from observation, interview, and documentation. The research was validated from triangulation. The analysis was through data reduction, presentation, and conclusion. The used theory is the theory of aesthetics. The research founds that (1) nanyin has the unique tone of music in the instrument and vocal tone; (2) the music uses simple melody with pentatonic bar; (3) the pitch is higher in each filler of dizi instrument part; (4) nanyin is performed in a dynamic tone; (5) most instrument plays some lyrical song; and (6) the performer wears cheongsam or dang zhuang during the performance.